"Good wood on crowdpleasers": humour publications in the Ming Wanli period - Smith Rosser, E (2021)
Joke and humour publications are a severely understudied area of the world of late-Ming book culture. Taking imprints from the Wanli reign period (1573–1620) as a starting point, this dissertation undertakes a preliminary investigation into late-Ming humour compilations. It looks at the publication of humour as a historical phenomenon, rather than from a literary standpoint, to see how this group of books fitted into the publishing and intellectual scene of their day. Towards this aim, the dissertation leans mostly upon the paratextual materials of humour publications, such as prefaces, titles and annotations. These were spaces in which compilers and publishers communed with their faceless, anticipated readership, and as such can be used to yield information about how these compilations were viewed on both sides. Experimenting by temporarily putting aside modern notions of “the joke” in favour of contemporaneous terms used by the publications themselves, the dissertation sketches the boundaries around a broader genre of ‘humour compilations’, thereby reconstructing a genre of publications that were connected in the eyes of Ming publishers and readers, yet has been obscured by subsequent systems of categorisation. It spotlights the ambivalence that surrounded humour as an appropriate topic for publication and the measures taken by compilers and publishers to counter such attitudes. The dissertation also sheds light upon how this group of texts identified with and drew upon precedents from previous dynasties and developed its own set of traditions through an in-depth look at the Ming sequels to the Aizi (“Master Ai”) tradition of Warring States-themed humour, which originated in the Song period. A preliminary discussion on the ‘Dongpo vogue’ in late-Ming publishing reveals the omnipresence of Song dynasty literatus Su Shi in Ming humour publications while simultaneously demonstrating how this group of texts reflected and interacted with the fashions and concerns of the times.